The Effect Perceived Supervisor Trust on Organizational Commitment: The Mediating Role of Job Burnout - Nadia Iga Pramesty; Ignatius Soni Kurniawan; Nala Tri Kusuma (Dinasti Publisher, 2025)
Employee welfare and the quality of relationships between leaders and subordinates are widely recognised as essential determinants of organisational success. These factors play a critical role in shaping employees’ attitudes, particularly their level of organisational commitment. In line with this perspective, this study aims to examine the effect of perceived superior trust and job burnout on organisational commitment, as well as to determine whether perceived superior trust influences job burnout. This study involved all 45 employees of PT Yogyakarta Tugu Televisi as respondents, representing the entire population. Data were collected through questionnaires and analysed using the Partial Least Squares–Structural Equation Modelling (PLS-SEM) approach. Before hypothesis testing, the reliability and validity of the research instruments were verified. Model evaluation included model fit testing, R-square values, effect sizes (f²), and bootstrapping procedures. The results showed that perceived superior trust had a significant effect on organisational commitment, and job burnout also had a significant effect on organisational commitment. However, perceived superior trust did not have a significant effect on job burnout. These findings confirm that relationships built on trust can strengthen employees’ commitment to the organisation, while job burnout serves as a determining factor in how well employees can sustain that commitment.